Level of spirituality of patients with breast cancer (Salud, Arte y Cuidado, 2019)
The objective of this study was to determine the level of spirituality of patients with Breast Cancer. This research is located in the paradigm quantitative, positivist, non-experimental, descriptive supported with field design, cross. The sample was comprised of 15 patients; whose medical diagnosis is Breast Cancer treated with chemotherapy and radiation therapy in the Oncology service, without delimitation in treatment time, who informed consent was applied for data collection an instrument of scale of perspective spiritual (SPS) Reed, p. (1991), validated and an alpha of Crombach of 0.90. The instrument consists of 10 items distributed in two-dimensional represented on two subscales: spiritual practices (items 1-4) and spiritual beliefs (items 5-10). The results in the dimension spiritual practices according to the scale of the instrument correction 94% found in the very high level of spirituality and 6% in regular spiritual level and dimension 80% spiritual beliefs are at the very height of spirituality and 20% in high level of spirituality. It is concluded that according to the scale general variable spirituality, 86% are at level very high spirituality and 7% in a high and consistent level of spirituality.
Keywords: spirituality; breast cancer; nursing